Investigation of swirl pipe for improving cleaning efficiency in closed processing system - LI, Guozhen (2016)
This thesis provides unique insights into the fundamentals of improving the efficiency of ‘Clean-In-Place’ procedures in closed processing systems by locally introducing intensified hydrodynamic force from swirl flows induced by an optimised four-lobed swirl pipe without increasing the overall flow velocities.